SOIL PROPERTIES AND GROWTH PERFORMANCE OF RIZE (Oryza sativa L.) GROWN IN A FLY-ASH AMENDED SOIL - Priatmadi, Bambang Joko; Saidy, Akhmad Rizali; septiana, Meldia (TROPICAL WETLAND JOURNAL, 2015)
Fly-ash (FA) is largely alkaline in nature and contains many essential elements for plant growth along with toxic metals.  Therefore, fly-ash is potential to be applied as soil ameliorate that may improve soil properties and plant growth.  In this experiment we studied the changes in chemical properties and rice production  of acid sulphate soils amended with fly ash.  Six different amounts of FA, viz. 0 (100% soil), 5, 10, 20, 40 and 75 tones FA ha-1 were added homogenously to 6 kg of soils in pots of PVC and then chemical properties of acid sulphate soils were observed after a 3-week of incubation. Subsequent of  the observation of soil properties, rice was planted onto the pots.  Results of study showed that fly-ash application improved soil pH and exchangeable Ca.  However, the availability of nitrogen of acid sulphate soils decreased significantly with fly-ash application.  The experiment also showed that fly-ash application to soils improved rice growth (height plant, number of tillers, dried-weight root and dried-weight shoot) and rice production. Application 20 tones FA ha-1 resulted in higher rice production than the application 0, 5 and 10 tones FA ha-1, and increasing subsequent the amount of FA application did not significantly increase the rice production. Results of this study demonstrate that low-level fly-ash application resulted in the improvements of soil chemical properties and rice production.Key words: fly-ash application; soil ameliorant; heavy metals; sub-optimal low land.